Extraordinary - Franklin, Miriam Spitzer (New York : Scholastic Inc., 2015)
"After she hears that her disabled best friend Anna might be able to have a surgery that will restore her to her old self, Pansy decides to overcome her fears and do anything to become extraordinary in time for Anna's return." (Source: WorldCat)